Peranan Wilayathul Hisbah dalam Meminimalisir Pelaku Khalwat di Kabupaten Aceh Tengah The Role Of Wilayathul Hisbah In Minimizing The Civilizers In The Central Aceh District - Syahputra, Syahputra; Kadir, Abdul; Hasibuan, Muhammad Aswin (Universitas Medan Area, 2017)
Aceh is the first entry point of Islam in Southeast Asia, precisely in Peurlak East Aceh on 1 Muharram 225 Hijrah. The term